Impact of Drying Temperature and Duration on Nutritional, Functional, and Microbial Qualities of Almond Bagasse. - TRAN, KHUE MINH; HOANG, OANH THI (Current Research in Nutrition & Food Science, 2025)
Dehydration is an important post-processing approach that stabilizes plant-based food residues and supports their transformation into powdered ingredients with improved shelf life and preserved nutritional quality. Almond bagasse, a nutrient-rich by-product of almond milk production, shows promising potential for food applications, especially in powdered form for bakery and gluten-free formulations. This study attempted to assess the impacts of drying temperature and duration on the nutritional, physicochemical, and microbial qualities of almond bagasse, supporting the selection of suitable processing parameters in its valorization. Four drying treatments were applied: Three single-stage conditions (80 °C or 120 °C for 2-3 hours) and a two-stage step-down process (120 °C for two hours followed by 80 °C for one hour). Carbohydrates, fat, crude fiber, and protein contents were statistically comparable (p > 0.05) between treated and raw samples, indicating minimal nutritional loss during drying. Nevertheless, increasing drying temperature and extending duration resulted in significant loss of vitamin C (29.2% to 61.4%). Drying conditions had limited effects on solubility and pH but significantly influenced swelling power (p<0.05). Oleic acid remained dominant (up to 40.8%), and both its content and the oleicto-linoleic acid ratio increased with thermal treatment, suggesting improved lipid stability and resistance to oxidative degradation. Drying conditions significantly reduced the initial microbial load and improved microbial stability during 15 days of storage, particularly under higher temperature and extended drying durations. Thus, two-stage step-down drying process was found to be the most effective pre-treatment for improving both the nutritional and microbiological quality of almond bagasse.